Mudanças climáticas e impactos sócio-territoriais dos desastres glaciais na Cordilheira Branca, Peru - Anderson Ribeiro de Figueiredo; Jefferson Cardia Simões; Álvaro Luiz Heidrich; Rualdo Menegat (Confins)
This article discusses the history of natural disasters in the Cordillera Blanca, Peru, during the 1970–2011 period. The study analyzed general disaster data over this timeframe and more broadly about glacial disasters from 1725 to 2010 AD. Historically, the region has been affected by a series of glacial disasters that left more than 26,000 people dead. Thus, this article examines the impact of these glacial disasters, considering that they trigger processes of deterritorialization and reterritorialization in the region. The following methodological strategies were adopted: fieldwork; semi-structured interviews conducted with glacial disaster survivors and environmental managers; literature review on the subject. We propose that climate change increases the risk of glacier-related disasters. From these reports, it has been possible to verify that deterritorialization implies the affectation of the inhabitant’s daily life, the break of relations and links with the place. Moreover, glacial disasters cause a process of abrupt deterritorialization and, consequently, a reterritorialization that will develop more slowly, opening an intense field of disputes between the different involved actors, arousing social conflicts.